The Growth of m-Learning and the Growth of Mobile Computing: Parallel developments - Caudill, Jason G. (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2007)
m-Learning is made possible by the existence and application of mobile hardware and networking technology. By exploring the capabilities of these technologies, it is possible to construct a picture of how different components of m-Learning can be implemented. This paper will explore the major technologies currently in use: portable digital assistants (PDAs), Short Message Service (SMS) messaging via mobile phone, and podcasts via MP3 players.